National Curriculum 2013 and the ability of Teacher’s Professionalism to Apply It. - Payong, Marselus Ruben (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
National Curriculum 2013 (K-13) will be implemented for the primary and secondary education in Indonesia immediately.The most important factor for the succesful of K-13 implementation is the teacher’s professionalismand their preparation. Based on the results of the evaluation of student’s learning outcome by NationalTesting and the results of the teachers competence test (UKG) in pedagogical and professional competencethat held on 2015, it was concluded that K-13 will face the big problems to be successful. Therefore,the teachers should be prepared by the continuous professionalism development (CPD) programs. Keywords: curriculum, profesionalism, teacher